Modelling morphological response of large tidal inlet systems to sea level rise : dissertation : submitted in fulfillment of the requirements of the Board for Doctorates of Delft University of Technology and of the Academic Board of the UNESCO-IHE Institute for Water Education for the degree of doctor to be defended in public on Monday, 12 December 2011 at 15:00 hours in Delft, the Netherlands /: dissertation : submitted in fulfillment of the requirements of the Board for Doctorates of Delft University of Technology and of the Academic Board of the UNESCO-IHE Institute for Water Education for the degree of doctor to be defended in public on Monday, 12 December 2011 at 15:00 hours in Delft, the Netherlands. (2012) - Unknown
No abstract available